O uso de Recorrência na Educação Básica. - SÁ, Wagner de Jesus Pereira (2020)
This work deals with the Use of recurrence in basic education, with emphasis, mainly, on the study of linear recurrences of 1st and 2nd order, and their techniques used in problem solving. The work presents numerical sequence concepts that are of great relevance for the study of linear recurrences. It also highlights the importance of recursive thinking that serves as a foundation for solving problems in di erent areas of mathematics. Some theorem demonstrations were made associated with the studies of 1st and 2nd order linear recurrences so that they are used as tools for solving various problems and activities of basic education. We highlight di erent applications to show that the study of recurrence is an important ally in mathematical modeling and that its study is accessible to students of basic education, especially the olympics in mathematics. The expectation is that this work will serve as a motivator for teachers and students in solving mathematical problems and that the practice of recursive reasoning will be increasingly used in basic education.